Phlebiella ailaoshanensis sp. nov. (Polyporales, Basidiomycota) described from China - Huang, Ruo-Xia; Chen, Jun-Zhu; Wu, Jian-Rong; Zhao, Chang-Lin (Phytotaxa, 2019)
Phlebiella P. Karst. (1890: 271) (Polyporales, Basidiomycota) was typified by P. vaga (Fr.) P. Karst. (1890: 271), which is a cosmopolitan genus characterized by a combination of resupinate to effused basidiocarps, hymenophore smooth to ceraceous to subgelatinous, a monomitic hyphal structure with clamped generative hyphae, basidia pleural and basidiospores hyaline, thin- to thick-walled, warted, subglobose, ellipsoid, cylindrical and acyanophilous (Karsten 1890, Bernicchia & Gorjón 2010). So far about ten species have been accepted in the genus worldwide (Karsten 1890, Bondartsev 1953, Hjortstam & Larsson 1987, Roberts 1995, Bernicchia & Gorjón 2010).